Harmonic Impact in Induction Generator Voltage Using Thyristor Control Reactor - Suprihardi Suprihardi; Yaman Yaman; Zamzami Zamzami; Nelly Safitri (Universitas Ahmad Dahlan, 2018)
As commonly known that theload fluctuations that have been performed on an induction motor operated as an induction generator (IG) triggers unstable induced voltage and frequency. Asthe result, the load that receiving the power quality is not running properly and the efficiency is low. The problems that have beenmitigated in this research in such way is the stability of the voltage that generated by IG due to fluctuating loading, and the harmonics can be damped by single tuned due to the work of thyristors and non-linear loads. The used method is the Ziegler-Nichols method by measuring and testing the design of prototype to get the best performance in stabilizing the voltage by using thyristor control reactor (TCR). The results showed that the induced generator with single tuned filter and TCR to nonlinear load variation at 1618 RPM is maintained stably for the voltage and frequency. Although, 3rd order harmonics of voltage and current that has been tuned can be dampedby using THDI 8.36%. Furthermore, it can be said that the response that generated by voltage control system using proportionalintegral (PI) control in 1kW-4 poles three-phase IG with additional and reductionalload generated a stable response.